Stakeholder Engagement in Post-Conflict Countries : The Liberian Experience - Ofori- Atta, Nana Yaa (World Bank, Washington, DC, 2012)
In February 2006, the government of Liberia invited the World Bank Group to work with the country to implement a comprehensive multiyear advisory services program. The program is designed to support the growth of a vibrant domestic private sector in Liberia that can create employment, increase opportunities for growth, attract partners, and provide services for quality international investment. The private sector development program in postconflict Liberia is being implemented by the investment climate team for Africa on behalf of the World Bank Group. The team is managed by the International Finance Corporation (IFC) and draws staff and resources from across the World Bank Group and development partners to help governments in Africa achieve successful reform. Underpinning the team's approach in Liberia is a deliberate strategy to engage with the government and all other key stakeholders, including civil society, the media, and the private sector. In the case of Liberia, this is all the more important, given the fine balance of power between the ruling party and the opposition. This Smart Lesson is intended to share the approach used by the team in Africa to develop and implement a concerted stakeholder engagement effort.